2011
DOI: 10.1177/0091270010368411
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Gabapentin in a Novel Gastric-Retentive Extended-Release Formulation: Comparison With an Immediate-Release Formulation and Effect of Dose Escalation and Food

Abstract: The objectives of the 3 phase I studies described herein were (1) to compare the pharmacokinetics of gabapentin delivered from a novel gastric-retentive dosage form vs an immediate-release formulation, (2) to assess the dose proportionality of the gastric-retentive extended-release formulation, and (3) to determine the effect of food on the pharmacokinetics of gabapentin delivered from this formulation. The time to reach maximum plasma concentration (t(max)) was extended for gabapentin delivered from the gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…The tablets incorporate Acuform ® technology (Depomed, Inc., Newark, CA, USA), which is designed to use release- controlling polymers that allow the tablet to remain in the stomach for several hours 29. This technology provides release of medication in the upper gastrointestinal tract at a controlled rate for an extended period of time 29–31. Each ER OC/APAP tablet contains high molecular-weight polyethylene oxide (Polyox ® ; Dow Chemical Company, Midland, MI, USA) as a swellable release-controlling polymer, which imparts gastric-retentive properties to the dosage form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tablets incorporate Acuform ® technology (Depomed, Inc., Newark, CA, USA), which is designed to use release- controlling polymers that allow the tablet to remain in the stomach for several hours 29. This technology provides release of medication in the upper gastrointestinal tract at a controlled rate for an extended period of time 29–31. Each ER OC/APAP tablet contains high molecular-weight polyethylene oxide (Polyox ® ; Dow Chemical Company, Midland, MI, USA) as a swellable release-controlling polymer, which imparts gastric-retentive properties to the dosage form.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, both calorie and fat content have been shown to affect the PK of drug products using the same Acuform ® technology (eg, Gralise ® ; Depomed, Inc.) 31. Given the possibility of a food-related PK effect with this formulation of OC/APAP, assessing the effect of food intake on ER OC/APAP was warranted.…”
Section: Introductionmentioning
confidence: 99%
“…28 Possible explanations for the relatively low incidence of AEs (dizziness, 10%; somnolence, 2.5%) with long-term treatment observed in this study may be attributed to the gastroretentive technology of the gabapentin dosage form allowing for both a longer delivery time and a slower delivery rate with a flatter and delayed peak plasma concentration of gabapentin. 18 In addition to the dosing regimen, administering the larger dose at night so that dizziness and somnolence would be less bothersome as the plasma concentration would peak in the late evening or when the patient is asleep. Future research that directly compares the efficacy and AEs associated with gabapentin versus G-GR would help to clarify the role that the gastroretentive technology has on AEs with gabapentin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…16 This controlled and slow release of drug attenuates the saturation of the transport mechanism of gabapentin and also enables the drug to be administered once, or twice daily while providing equivalent or improved bioavailability compared with immediate-release gabapentin administered 3 or more times daily. 17,18 Previous short-term (r10 wk) studies with G-GR, administered once or twice daily, for the management of PHN showed a low incidence of AEs, particularly dizziness and somnolence. [19][20][21] The current study evaluated the longterm safety and tolerability of G-GR and its effect on weight gain in PHN patients treated with G-GR for a total of 24 weeks.…”
mentioning
confidence: 99%
“…OC/APAP ER tablets employ a dual-layer biphasic delivery mechanism that, when administered as a single dose (i.e., two tablets; 15 mg OC/650 mg APAP), is designed to deliver 3.75 mg OC/325 mg APAP through the IR component and 11.25 mg OC/325 mg APAP through the ER component. The ER delivery technology utilizes the Acuform drug delivery systemz containing hydrophilic polymers that release the active ingredients at a steady rate into the upper gastrointestinal tract over an extended period [30][31][32] . This technology may also contribute to potential tamperresistant and abuse-deterrent properties of OC/APAP ER, which was demonstrated in in vitro 33 and phase 1 studies 34 .…”
Section: Please Scroll Down For Articlementioning
confidence: 99%